2021
DOI: 10.1016/j.ijrobp.2021.01.045
|View full text |Cite
|
Sign up to set email alerts
|

ATM Variants in Breast Cancer: Implications for Breast Radiation Therapy Treatment Recommendations

Abstract: Purpose: Advances in germline genetic testing have led to a surge in identification of ataxia-telangiectasia mutated (ATM ) variant carriers among breast cancer patients, raising numerous questions regarding use of breast radiation therapy (RT) in this population. Methods: A literature search using PubMed identified articles assessing association(s) between the germline ATM variant status and the risk of toxicity after breast RT. An expert panel of breast radiation oncologists, genetic counselors, and basic sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 64 publications
0
8
0
2
Order By: Relevance
“…They found that younger patients were more likely to have a long-term risk of breast cancer (32). Macduff et al evaluated patients below 45 years who were carrying certain rare ATM variants, and they should be more aware of the risk of SCCP of CB cancer (33). This led us to analyze the secondary incidence of breast cancer using the T-VMAT technique, and the SCCP of CB was significantly higher than that in the other two techniques.…”
Section: Discussionmentioning
confidence: 99%
“…They found that younger patients were more likely to have a long-term risk of breast cancer (32). Macduff et al evaluated patients below 45 years who were carrying certain rare ATM variants, and they should be more aware of the risk of SCCP of CB cancer (33). This led us to analyze the secondary incidence of breast cancer using the T-VMAT technique, and the SCCP of CB was significantly higher than that in the other two techniques.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, radiotherapy via speculation has not been recommended as first line due to concern over loss of a tumor suppressor gene CLYD1, which could induce further malignancy [9]. However, in other disease sites such as breast cancer, loss of important tumor suppressor genes such as ATM in it of itself is not a contraindication to receiving radiotherapy and does not demonstrate increase in normal tissue side effects [10]. Furthermore, despite basal cell carcinoma demonstrating loss of several tumor suppressor genes, including CLYD, radiation is still routinely used to manage certain lesions without increase in side effects [11].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Hinsichtlich einer pathogenen ATM-Mutation zeigen sich widersprüchliche Aussagen. Aktuell wird in der Literatur kontrovers diskutiert, ob eine Bestrahlung strahlenbedingte Schäden oder erneute Krebserkrankungen verursachen könnte [17,18]. Insbesondere bei jüngeren Patient*innen unter 45 Jahren geht man von einer signifikanten Risikoerhöhung aus.…”
Section: Strahlensensitivität Bei Keimbahnmutationenunclassified